Penggunaan Brand Franchise yang Putus Kontrak Akad Syirkah: Analisis Kasus Tea Tarik Halto Arcamanik Kota Bandung - Gomang, Sukardi; Ulum, Muhammad Saepul; Effendi, Rika Rosdiana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study stems from the misuse of the Tea Tarik Halto franchise trademark in Arcamanik, Bandung City, where the partner continued to use the attributes and brand unilaterally even though the contract had been terminated through mutual deliberation. This study aims to analyze the practice of unilateral contract termination and the use of the trademark after the end of cooperation in the Tea Tarik Halto Franchise Business in Arcamanik, Bandung City, as reviewed from the principles of fiqh muamalah. This study employed a descriptive qualitative method through a field study approach. Primary data were obtained through observation, in-depth interviews with related parties at Tea Tarik Halto Arcamanik, and documentation. Secondary data were derived from fiqh muamalah literature and related books. Data were analyzed using an inductive method by linking field facts with general theories of Islamic economic law. The results show that the syirkah contract in the franchise business is fundamentally in line with Islamic economic principles. However, the unilateral termination of cooperation carried out by the partner constitutes an unjustified act. From the perspective of fiqh muamalah, such conduct falls into the category of breach of contract and violates the principle of trustworthiness (amanah) in the agreement. The use of the brand without permission after contract termination is regarded as a form of breach of promise (al-wa’du), which is unlawful (haram), as it harms another party and does not fulfill the pillars and conditions for the continuity of syirkah.